Stratigraphy of the Mina Verdún Group, Proterozoic of Minas, Uruguay (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The aim of this contribution is to introduce the stratigraphic framework of the Mina Verdún Quarry, located in the eastern side of Verdún Hill, Minas, Uruguay (Fig. 1), and to characterise their sedimentary units. The paleoenvironments involved are outlined as well as the sedimentological significance of the very well developed stromatolites. The stratigraphic position and composition of this sedimentary succession used to be uncertain and the limestone from the Mina Verdún Quarry was alternatively considered part of diverse litostratigraphic units (Mac Millan, 1933; Caorsi and Goñi, 1958; Bossi et al., 1965; Midot, 1984; Preciozzi  et al., 1985; Bossi and Navarro, 2000; Sánchez Betucci, 1998; Sánchez Betucci et al., 2001).From the base to the top (Fig. 2), the sedimentary succession consists of the Mina Verdún Group, Las Palmas Formation and the quartzites of the Verdún Hill (Fig. 3). Mina Verdún Group (Poiré et al., 2003b) is conformed by:Don Mario Formation (Poiré et al., 2003b): 40 m thick, base not exposed; massive and laminated, black shales (Fig 4a), which are rich in organic matter (Fig. 5a). XRD analysis shows manly quartz, with scarce calcite, clay (illite, chlorite, and IS and CS interlayer) and feldspars (Fig. 6). Applying the Bhatia and Crook (1986), Taylor and McLennan (1985) and McLennan et al. (1990, 1993) plots (Fig. 7) their geochemistry suggests a high degree of weathering and reworking in the source area compose of a differentiated upper continental crust.La Toma Formation (Poiré et al., 2003b): 15 m thick; fine-grained, dark green marls (Fig. 4b and c), bearing up to 45 % of silica and 35 % of CaCO3. Petrographically they show micritic crystals of calcite and dolomite, quartz and feldspars (Fig. 5b); lamination is interrupted by stilolytes. Clay minerals are composed mainly by illite and scarce chlorite (Fig. 6).El Calabozo Formation (Poiré et al., 2003b): 170 m thick; grey massive, laminated, and stromatolite limestones (Fig. 4d), bearing up to 93 % of CaCO3 with some collapse breccias as resulting of probably karstic phenomena. In thin section they show homogeneous mosaic of micrite and subsparite calcite (Fig. 5 c and  d) with stilolites and corrugated stromatolite lamination. Very abundant calcite with rare quartz, feldspars and illite have been recorded by XRD (Fig. 6). This sedimentary sequence is affected by diagenetic features and a fragile deformation (cleavage foliation, shear zones) which are slightly hiding the stromatolite morphologies (Fig. 8), but the main features of the stromatolites from El Calabozo Formation are still well preserved. Columnar stromatolites assignable to Conophyton fm. are the most abundant group of these organic sedimentary structures. This Conophyton fm. consists of unbranching subcylindrical columnar stromatolites with strikingly conical internal laminae whose apexes define a distinctive axial zone (Figs. 10a, b, c) and their horizontal section display a conspicuously and regularly concentric structure (Figs. 10c, d, f). The internal laminae are commonly continuous from one column to another, in which case vertical sections show upward laminae apexing. Their profile is angulate to geniculate and their plant outline could be round circular to oblong, in which case the axes are strongly orientated. The attitude of the columns is usually straight but sometimes they adopt a recumbent and sinuous posture. The column height is up to 70 cm and the column width is 5 to 20 cm. However, scarce but preserved dendroid branching style stromatolites have been recorded on the field, as well as small, rounded plant outline columnar stromatolites have been observed in cores, which could represent digitate branching stromatolites. Five kilometres to the south, this stromatolitic limestone facies change to deformed laminate limestones (Figs. 4e, f). Furthermore, 40 km to south, the El Calabozo Formation bearing Conophyton stromatolites has been reported by Gaucher  et al. (2004a).Gibraltar Formation (Poiré et al., 2003b): 60 m, top not exposed; black marls and shales (Figs, 10a, b, c), pink limestones and dolomite limestones, and light yellow, green, reddish, black and grey dolomites (Fig. 10d, e). The unconformity between the El Calabozo and Gibraltar formations is very irregular, which is interpreted as a karstic palaeorelief. A 4 m thick diagenetic breccia is often in the base of the unit.The Mina Verdún Group is overlaid by red polymictic conglomerates and sandstones (Fig. 10f) of Las Palmas Formation (Poiré et al., 2003b) and is intruded by a subvolcanic longitudinal (E-W) dike swarm. This shows a K-Ar whole rock datum of 485,2 ± 12,5 Ma considered as a minimum cooling (Gonzalez  et al., 2004). The quarzites from the Verdún Hill are overlying these units by a tectonic contact. They have been assigned to the Cerro Espuelitas Formation by Gaucher (2000), which are Ediacarean in age.Sedimentological and stratigraphic implications The black shales and claystones of the Don Mario Formation are interpreted as fine deposits in a low energy environment with euxinic conditions, which becomes calcareous to form a carbonatic ramp (La Toma Formation). The latter shows and evolution to a carbonatic algae platform very rich in stromatolites. From a sedimentological point of view, the group Conophyton has been assigned as a deep subtidal stromatolite by Poiré (1987, 2002) based on Precambrian stromatolite cycles from Villa Mónica Formation, Buenos Aires Province, Argentina, and Logan et al. (1964) and Donaldson (1976) ideas. In this sense, the low biodiversity, Conophyton abundance and the plant view axes orientation allow to suggest a subtidal marine environment for the El Calabozo Formation, with tidal currents influence (Fig. 11). The strong dolomitization of the Gibraltar Formation and their poor exposure do not allow doing detailed interpretation about paleoenvironments.The age of the Mina Verdún Group is Precambrian but there are not major precisions about that. Unfortunately, the group Conophyton has a wide range during the Precambrian, from Early Proterozoic to Ediacarean, being impossible to define the age of these limestones. More detailed future studies about microstructure of this Conophyton could be useful to distinguish the taxonomy and to determinate its possible age.Pre-Ediacarean stromatolites have also been described 30 km to the north by Sprechmann et al. (1994) and Gaucher et al. (1996) in the Villalba Formation of the Basal Group (Gaucher y Sprechmann, 1995), but their morphologies are completely different. They have recorded stratiform, nodular-stratiform (LLH-C, LLHV) and columnar (SH-V) stromatolites associated with stromatolitic breccias, which were interpreted as intertidal to supratidal deposits. It could represent shallower stromatolite assemblages than the stromatolites from the Mina Verdún. Unfortunately, there are no radiometric data to prove this idea.Very well developed Conophyton ?ressotti and Conophyton fm. have been also recorded in the dolomites of the Villa Mónica Formation (Poiré, 1993) companied  by Colonella fm., Cryptozoon fm., Gongylina fm., Gymnosolem fm., Inzeria fm., Jacutophyton fm., Jurusonia nisvensis, Katavia fm., Kotuikania fm., Kussiella fm., Minjaria fm., Parmites fm., Parmites Cf. cocrescens and Stratifera fm. (Poiré, 1989 y 1993), which radiometric age for diagenesis is 795 My (Cingolani y Bonhomme, 1988). This sequence could be correlated with El Calabozo Formation but it shows a poor biodiversity.The Mina Verdún Group is considered as a new lithostratigraphic unit in the Uruguayan stratigraphic framework, which is probably located somewhere between the Basal and Arroyo del Soldado groups